Supercooled phase transitions in conformal dark sectors explain NANOGrav data - Gonçalves, João; Marfatia, Danny; Morais, António P.; Pasechnik, Roman (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
According to recent lore, it is difficult to explain the evidence for a stochastic gravitational wave background obtained by pulsar timing arrays with supercooled first-order phase transitions (FOPTs). We demonstrate that supercooled FOPTs in dark U(1)′ models with a conformal dark sector easily explain the nHz signal at NANOGrav.
Keywords: Conformal models; Dark sectors; NANOGrav; Supoercooled phase transitions